2018
DOI: 10.3310/hta22560
|View full text |Cite
|
Sign up to set email alerts
|

Two interferon gamma release assays for predicting active tuberculosis: the UK PREDICT TB prognostic test study

Abstract: Background Despite a recent decline in the annual incidence of tuberculosis (TB) in the UK, rates remain higher than in most Western European countries. The detection and treatment of latent TB infection (LTBI) is an essential component of the UK TB control programme. Objectives To assess the prognostic value and cost-effectiveness of the current two interferon gamma release assays (IGRAs) compared with the standard tuberculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 92 publications
1
35
0
4
Order By: Relevance
“…Intriguingly, our data indicate individual level risk stratification may be possible using T-cell assays, including the standardised assay kits used in this study which, being in the same format as the widely used T-SPOT®. TB tests for latent TB infection, would be readily deployable at scale (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, our data indicate individual level risk stratification may be possible using T-cell assays, including the standardised assay kits used in this study which, being in the same format as the widely used T-SPOT®. TB tests for latent TB infection, would be readily deployable at scale (24).…”
Section: Discussionmentioning
confidence: 99%
“…The test is similar to the widely deployed T-SPOT ® . TB test, which identifies patients infected with M. tuberculosis (24).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PTB were also recruited at Guy’s and St Thomas’ and Royal Free London NHS Foundation Trusts, London UK (low TB incidence site; designated group UKPTB (n = 63)). Individuals with suspected LTBI (n = 103) and matched negative controls [CNTRLB (n = 102)] were recruited from individuals variably-domiciled in the UK and Asia, resident in the greater London area as part of the UK PREDICT TB study, i.e ( 4 , 42 )., by Public Health England Centre for Infections, 61 Colindale Avenue London and University College, London UK. This was a prospective cohort study, recruiting participants from 54 centers in London, Birmingham, and Leicester, at high risk for latent tuberculosis infection (i.e., recent contact with someone with active tuberculosis [contacts] or a migrant who had arrived in the UK in the past 5 years from-or who frequently travelled to-a country with a high burden of tuberculosis [migrants]).…”
Section: Methodsmentioning
confidence: 99%
“…Mycobacterium tuberculosis (MTB), the causative agent of tuberculosis (TB) is the leading cause of infectious disease worldwide ( 1 , 2 ), accounting for the deaths of approximately 1.3 million people each year ( 3 ). The United Kingdom (UK) has seen an increase in TB since the late 1980s, with rates higher than the rest of Europe ( 4 ), and there are currently around 6000 new cases each year ( 5 ). In 2016, 73.6% of confirmed TB cases in the UK were foreign-born, with India and Pakistan the most frequent countries of origin ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…A very recent study also found no difference in the prevalence of LTBI in the UK, where the relative incidence between BCG vaccinated and naïve people was compared (47). Another very recent report predicted the possible estimation of the role of BCG vaccination on reactivation from LTBI, but the final outcome is yet to be reported (48). In a statistically underpowered Taiwanese study the percentage of T-SPOT.TB positive, HIV-infected patients, was almost 50% less in people showing a BCG scar compared with those with no evidence of BCG vaccination, therefore suggesting BCG reduces reactivation from LTBI in a HIV setting (49).…”
Section: Introductionmentioning
confidence: 99%